Differences in non-high density lipoprotein levels, blood pressure and waist circumference between normal-weight obesity, lean, and obese women - Winda Angriani; Desmawati Desmawati; Aisyah Elliyanti (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition)
Background: Normal Weight Obesity (NWO) is a condition characterized by an average Body Mass Index (BMI) with high body fat percentage (BFP≥30%), distinct from individuals with normal BMI and normal body fat (BFP <30%), known as Normal Weight Lean (NWL). NWO is associated with an increased risk of cardiovascular diseases, dyslipidemia, and central obesity.